Permasalahan Yang Dihadapi Guru Dalam Pengelolaan dan Pemanfaatan Media Pembelajaran - Prastika, Dwi; Hawanti, Santhy; Mareza, Lia (Universitas PGRI Adi Buana Surabaya, 2019)
The main focus of this research is the problem of the management and use of instructional media by teachers. This study aims to determine the teacher & problems in the management of instructional media and find out the teacher & problems in utilizing instructional media as a source of learning in State Elementary School 2 Kalisalak. In this study using a descriptive qualitative approach and data collection techniques include observation, interviews, and documentation. The results of the study show that the teacher & problematics in managing the media for procurement provided by schools is incomplete, so each teacher chooses by designing the media and utilizing the surrounding environment to be used as media, inventory recording is still united with the needs of the school, there is no special room for storage of learning media, and the storage is still lacking maintenance, because there is no special staff to handle media storage. The next result is the problematic teacher in the use of instructional media, in the learning process low-grade teachers more often use the surrounding environment as a medium of learning, the LCD media but only a few teachers can use the LCD.